Pengaruh Kemudahan Penggunaan, Kepercayaan, dan Kepuasan Terhadap Loyalitas Pelanggan Maxim di Kota Batam - Chelsea Amelia; Suhardi Suhardi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was conducted to analyze the extent to which ease of use, trust, and customer satisfaction contribute to customer loyalty of the Maxim online transportation service in Batam City. The approach used was a quantitative method with a descriptive research design, which focuses on systematically and measurably testing causal relationships between variables. The research subjects involved 100 respondents who were active users of the Maxim application and had experience using the service repeatedly. The sampling technique was applied through purposive sampling with consideration of the Lemeshow approach to ensure the adequacy and statistical power of the sample. Data processing was carried out through several stages of analysis, including testing the validity and reliability of the research instrument, classical assumption testing, multiple linear regression analysis, and hypothesis testing to identify the contribution of each independent variable to customer loyalty. The results indicated that ease of use contributed 55.0% to customer loyalty, trust contributed 15.3%, and customer satisfaction contributed 10.3%. Simultaneously, these three variables were able to explain 83.4% of the variation in Maxim customer loyalty based on the coefficient of determination (R²), while the remainder was influenced by other factors outside the research model. Thus, it can be concluded that ease of use, trust, and customer satisfaction, both partially and collectively, have a significant influence on increasing Maxim customer loyalty in Batam City.